Pengaruh ROA, FDR terhadap CAR Keuangan Bank Umum Syariah dan Unit Usaha Syariah di Indonesia - Renny Mointi; Syahribulan syahribulan; ady Kurnia (Economy Deposit Journal (E-DJ), 2022)
The purpose of this study is to identify the effect of Return on Assets (ROA), Financing to Deposit Ratio (FDR) on the Capital Adequacy Ratio (CAR) of Islamic Commercial Banks and Sharia Business Units in Indonesia. The independent variables of this study were ROA (X1) and FDR (X2), and the dependent variable was CAR (Y). This is a quantitative analysis that was conducted in 2019 from January to December using secondary data that has previously been released. The population of this research is the financial ratios of Islamic commercial banks and my business units acquired from the Financial Services Authority's statistical reports on Islamic banks issued in 2019 utilizing Time series data. This original study test is multiple linear regression, which is measured with Stata 16. The Common Effect model was selected for this study based on the model accuracy test and the classical assumption test with normality, heteroscedasticity, and multicollinearity test methods. According to the results of a study, ROA and FDR have a positive relationship to CAR. CAR will grow for every 1% increase in ROA, and CAR will increase for every 1% increase in FDR. The independent variable is simultaneous and has no effect on the dependent.